Acculturation and alcohol: Exploring experiences of alcohol for Asian international students in Australia. (November 2021) - Bhat, Priyanka; Dwyer, Robyn; Vally, Hassan; Pennay, Amy
Abstract: Acculturation can be a challenging experience for Asian international students moving to Western countries for study. The majority of international students are young adults, a population that has recently entered the legal alcohol purchase age, and who might not be familiar with new regulatory contexts and socio-cultural environments where drinking is common. Informed by theories of acculturative stress, ethno-identity conflict and adaptation, we explored 15 Asian international students' lived experiences of alcohol in Australia, and the social, cultural and religious contexts within which these experiences were situated. Semi-structured interviews were undertaken, with an Interpretative Phenomenological Analysis exploring subjective experiences of alcohol and acculturation processes. Participants articulated numerous and varied experiences of their transitions, however, did not draw connections between stressful transition experiences and subsequent drinking. Most participants reported having increased their drinking since arrival in Australia, and although many participants had adapted to Australian patterns of drinking and socialising, they also reported it was challenging to navigate different cultural and social expectations and values around alcohol that were strongly rooted as a part of their ethnic heritage. Our participants' experiences may be useful to inform future research on this much under-studied topic, as well as being used by universities to consider appropriate strategies for addressing alcohol-related acculturation processes as part of orientation curriculum with international students.